Pengaruh Kompensasi dan Beban Kerja Terhadap Kinerja Karyawan PT Agung Wijaksana Utama Sakti - Marga Yuda Firmansyah; Hartanti Nugrahaningsih; Muhammad Zakie Hanifan (Indonesian Journal of Innovation Multidisipliner Research, 2023)
The aim of this research is to determine the effect of savings and workload on the performance of PT Agung Wijaksana Utama Sakti employees in Jakarta. The method used by this researcher is a quantitative method using primary data. Data were collected using a questionnaire distributed to employees of PT Agung Wijaksana Utama Sakti in Jakarta with a total of 40 respondents. The results of data analysis using the SPSS Version 26 application, the data analysis method using correlation and regression, the results are as follows: Results of X1 for Y produce R = 485, Results of X2 for Y produce R = 259, Results of X1 and The partial hypothesis t test shows tcount = 3.423 > ttable = 1.685, meaning there is a relationship between improvement and performance. The partial hypothesis test is tcount = 1.782 > ttable = 1.685. This means that there is an influence between workload and performance. Hypothesis test Fcount = 6.574> Ftable = 3.25 then Ho is rejected (Ha is accepted), meaning that there is an influence between compensation and workload together on employee performance.